Dirk Gently's Holistic Detective Agency - Adams, Douglas, 1952-2001 (Dirk Gently trilogy, 2014)
Quirky and bumbling private investigator Dirk Gently stumbles upon a ghost, millions of years old, wandering the earth and disturbing its people. Dirk soon discovers this phantom yearns for more than a good haunting: it is desperately trying to go back in time to prevent its own death. But this ghost was no ordinary person, and helping it save itself just might change the modern world as we know it. And not in a good way!